Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1046/j.1445-2197.2002.02501.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent twitching of the Latissimus Dorsi muscle after a posterolateral thoracotomy

Abstract: We report a case of persistent twitching of the latissimus dorsi muscle following a posterolateral thoracotomy, which continued despite several attempts at control including denervation, and was ultimately cured by total resection of the muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Six months after posterolateral thoracotomy and after the start of PTPS our patient presented a continuous involuntary jerk-like movement of the right latissimus dorsi muscle – its distribution was clearly defined by the right thoracodorsal nerve. Four years after these involuntary movements appeared, we proved that they showed clinical and electromyographic hallmarks of previously reported cases with appearance of jerks due to thoracodorsal nerve injury after thoracotomy ( Aslam et al, 2009 , Belluzzo et al, 2015 , Carnero‐Pardo et al, 1998 , Hao and Clarke, 2002 ). The duration of these EMG discharges may range from 50 ms to 200 ms or, as it happens in our case, can even be longer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Six months after posterolateral thoracotomy and after the start of PTPS our patient presented a continuous involuntary jerk-like movement of the right latissimus dorsi muscle – its distribution was clearly defined by the right thoracodorsal nerve. Four years after these involuntary movements appeared, we proved that they showed clinical and electromyographic hallmarks of previously reported cases with appearance of jerks due to thoracodorsal nerve injury after thoracotomy ( Aslam et al, 2009 , Belluzzo et al, 2015 , Carnero‐Pardo et al, 1998 , Hao and Clarke, 2002 ). The duration of these EMG discharges may range from 50 ms to 200 ms or, as it happens in our case, can even be longer.…”
Section: Discussionsupporting
confidence: 76%
“…During these types of surgeries, although less frequent, thoracodorsal and long thoracic nerves can also be injured. As a consequence of partial nerve injury, jerks of the muscle innervated by the injured nerve may appear usually between several days and several years after the surgery ( Aslam et al, 2009 , Belluzzo et al, 2015 , Carnero‐Pardo et al, 1998 , Hao and Clarke, 2002 , Lagueny et al, 2014 ). Long series of post-thoracotomy intercostal neuralgia and several cases of post-thoracotomy jerks of the serratus anterior or of the latissimus dorsi muscle have previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The muscle acts as the shoulder extensor, adductor and internal rotator. The nerve supply is via the thoracodorsal nerve running deep to the muscle [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The LD flap is one of the most widely used flaps in reconstructive surgery, owing to its wide vascular diameter and lengthy dependable size [9,50]. Common complications after LD flap breast reconstruction surgery may involve muscular contraction causing postoperative pain and breast contour deformities [48,51]. Several studies have suggested that intraoperative resection of the thoracodorsal nerve should be performed to prevent involuntary LD muscle spasm following breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread use of the pedicled latissimus flap for breast reconstruction, management of the thoracodorsal nerve remains poorly discussed in the literature, and as a result, there remains no best practice guidelines to dictate whether and when nerve transection is indicated. Recommendations in the available literature vary widely, with some authors recommending immediate nerve transection at the time of reconstruction, others suggesting transection is only indicated as a secondary procedure for symptomatic patients, and still others advising the nerve should be spared . The results of many published studies must be interpreted with caution, however, as the length of follow‐up is short, and the anatomical site of nerve transection is often not reported.…”
Section: Discussionmentioning
confidence: 99%